Patient‐specific establishment of bacterial composition within the peri‐implant microbiota during the earliest weeks after implant uncovering. (31st May 2021) - Shimogishi, Masahiro; Watanabe, Takayasu; Shibasaki, Masaki; Shiba, Takahiko; Komatsu, Keiji; Nemoto, Takashi; Ishihara, Kazuyuki; Nakano, Yoshio; Iwata, Takanori; Kasugai, Shohei; Nakagawa, Ichiro
Abstract: Background and Objective: Dysbiosis, a loss of balance in the microbiota, is a potential factor of peri‐implantitis. However, compositional change of the peri‐implant microbiota soon after implant uncovering is still unknown. In this study, bacterial composition in the peri‐implant sulcus was examined to understand the establishment of bacterial composition within the peri‐implant microbiota during the earliest weeks after implant uncovering. Methods: Microbiota samples were collected at weeks 1, 2, 4, and 6 after stage‐two surgery. Bacterial DNA was isolated from the samples, and a 16S rRNA gene library was constructed. Sequence reads were obtained using a high‐throughput sequencing platform and were taxonomically assigned at the phylum and genus levels. Results: Alpha diversity indices, which did not include taxonomic information, were at similar levels throughout the four time points. At 1 and 2 weeks, the bacterial composition was similar among patients with the predominance of Firmicutes and Proteobacteria . However, the composition was diverse at 4 and 6 weeks and significantly dissimilar to the composition at 1 week. Conclusions: At 1 week, the peri‐implant microbiota was already formed with alpha diversity as high as that at the later time points. However, the bacterial composition was not highly dissimilar among patients at 1 week. The composition changed over the passage of several weeks and was specific for each patient.